Analysis of The Influence of Brand Image and Negative Electronic Word of Mouth on Repurchase Intention of Ice Cream Aice Consumers - Syailendra Reza Irwansyah Rezeki; Fani Sartika; Tengku Kespandiar; Ita Nurcholifah; Wenny Desty Febrian (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The development of the internet in Indonesia is becoming increasingly widespread. One of the ice cream companies in Indonesia is experiencing negative electronic word of mouth due to internet developments. This study uses brand image as an intervention to examine the impact of unfavorable electronic word of mouth on repurchase intention. Purposive sampling was used to select 100 respondents and distribute questionnaires to them. Path analysis is the data analysis technique employed. The study's findings indicate that negative online reviews have little bearing on a brand's reputation. Negative online reviews affect consumers' intentions to make new purchases. Repurchase intent is influenced by brand perception. Repurchase intentions are impacted by negative brand perception and electronic word of mouth. By using brand image as an intermediary variable, negative electronic word of mouth has no impact on consumers' intentions to make another purchase.